2005
DOI: 10.1897/03-621.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in productivity and contaminants in bald eagles nesting along the lower Columbia River, USA

Abstract: Previous studies documented poor productivity of bald eagles (Haliaeetus leucocephalus) in the lower Columbia River (LCR), USA, and elevated p,p'-dichlorodiphenyldichloroethylene (DDE), polychlorinated biphenyls (PCBs), dioxins, and furans in eagle eggs. From 1994 to 1995, we collected partially incubated eggs at 19 of 43 occupied territories along the LCR and compared productivity and egg contaminants to values obtained in the mid-1980s. We found higher productivity at new nesting sites along the river, yet p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
(101 reference statements)
0
19
0
Order By: Relevance
“…Previous research , Buck et al 2005) and annual survey results (Isaacs and Anthony 2008) indicated that nesting success and productivity varied along the Columbia River. We compared those parameters by state, river segment and river mile by simple Chi-square tests on frequencies to quantify the differences and locate individual and groups of breeding areas with low productivity.…”
Section: Columbia River Segmentsmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous research , Buck et al 2005) and annual survey results (Isaacs and Anthony 2008) indicated that nesting success and productivity varied along the Columbia River. We compared those parameters by state, river segment and river mile by simple Chi-square tests on frequencies to quantify the differences and locate individual and groups of breeding areas with low productivity.…”
Section: Columbia River Segmentsmentioning
confidence: 94%
“…The Columbia was the only shared watershed where breeding areas in both states were included in our study area because the Columbia River corridor provided habitat for many nesting pairs, some breeding areas included portions of both states, and we monitored or coordinated monitoring of breeding areas on the Washington side of the river from 1996-2007. In addition, there have been concerns about the effects of environmental contaminants on the Columbia River subpopulation , Buck et al 2005. Watersheds were further subdivided into smaller areas (App.…”
Section: Recovery Zones and Watershedsmentioning
confidence: 99%
See 1 more Smart Citation
“…At sites furthest downstream on the LCR, sperm quality values in LSS were the lowest. Along a similar stretch of the LCR, the lowest bald eagle nest productivities were found at the river's mouth, where the highest concentrations of organochlorines in eggs occurred (Buck et al, 2005). Most PBDE are hydrophobic, lipophilic, and have half-lives on the order of 1-20 years or more.…”
Section: Fish and Sitesmentioning
confidence: 96%
“…In the North Pacific Ocean, adults can bioaccumulate persistent organic pollutants which are then biotransported into freshwater by the migrating fish, their roe, and later their degrading carcasses. During the migration, organohalogens are transferred from fat to muscle (Cullon et al, 2009;Svedsen et al, 2007), which can then be consumed by foraging biota (Ewald et al, 1998) including bald eagles (Haliaeetus leucocephalus) (Buck et al, 2005), great blue herons (Ardea herodias) (Thomas and Anthony, 1999), and osprey (Pandion haliaetus) (Henny et al, 2011). Along the LCR, spatial differences exist in the concentrations of persistent organic pollutants as shown by PBDE concentrations in osprey eggs (Henny et al, 2011).…”
Section: Introductionmentioning
confidence: 99%